Power Relations in Scorpio City by Mario Mendoza - Fuentes Bayona, Adriana Yiseth (Rastros Rostros, 2013)
Power is one of the most recurrent themes in the work of Mario Mendoza, and in the Colombian noirnovel in general, since one of the characteristics of novels in this genre is social critique. Hence, thisarticle conducts a hermeneutical analysis of power relations and mechanisms in Mario Mendoza’s novelScorpio City, based on the study of power by French philosopher Michel Foucault. The analysis showsthe underlying power structures in the religious, sexual and persuasive discourses that the hero of thenovel comes into contact with.
Keywords: foucault; Colombian literature; Mario Mendoza; crime novel; power relations